Patient satisfaction with nursing care in an emergency service - Levandovski, Patrícia Fátima; Dias da Silva Lima, Maria Alice; Marques Acosta, Aline (Investigación y Educación en Enfermería, 2015)
Objective. To analyze patient satisfaction with nursing care received at a hospital emergency service. Methodology. This is a quantitative, descriptive, cross-sectional study. The sample was composed by 250 patients over 18 years old who used an emergency service in the south region of Brazil. Data were collected using an identification form and the Patient Satisfaction Instrument. Results. Results point to a good level of satisfaction of patients with the nursing care received, with the greatest mean found in the technical-professional care domain. Satisfaction was significantly associated with the room where the patient was and correlated to age, education and the length of stay in the service. Conclusion. It was concluded that patients have good level of satisfaction with the care provided by nurses in emergency service. How to cite this article: Levandovski PF, Lima MADS, Acosta AM. Patient satisfaction with nursing care in an emergency service. Invest Educ Enferm. 2015; 33(3):